2021
DOI: 10.1016/j.apmr.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Adherence to OnabotulinumtoxinA Treatment for Spasticity: Insights From the ASPIRE Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23] The real-world, multicenter, prospective, Adult SPasticity International REgistry (ASPIRE) study (NCT01930786) examined the patterns of real-world onabotulinumtoxinA utilization in the clinical setting and assessed the effectiveness of onabotulinumtoxinA treatment for spasticity. 15,16,24,25 Findings of ASPIRE demonstrated that among the 484 patients who received ≥1 treatment of onabotulinumtoxinA for UL spasticity, stroke was the most frequently reported underlying etiology (74.0% of patients) and clenched fist was the most commonly treated UL clinical presentation (79.1% of patients). 15 Across all presentations, the dose of onabotulinumtoxinA treatment ranged from 5 to 600 U, and treatment use varied by presentation.…”
Section: What Is Newmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] The real-world, multicenter, prospective, Adult SPasticity International REgistry (ASPIRE) study (NCT01930786) examined the patterns of real-world onabotulinumtoxinA utilization in the clinical setting and assessed the effectiveness of onabotulinumtoxinA treatment for spasticity. 15,16,24,25 Findings of ASPIRE demonstrated that among the 484 patients who received ≥1 treatment of onabotulinumtoxinA for UL spasticity, stroke was the most frequently reported underlying etiology (74.0% of patients) and clenched fist was the most commonly treated UL clinical presentation (79.1% of patients). 15 Across all presentations, the dose of onabotulinumtoxinA treatment ranged from 5 to 600 U, and treatment use varied by presentation.…”
Section: What Is Newmentioning
confidence: 99%